Peningkatan Reputasi dan Citra Rumah Sakit Melalui Strategi Humas - Maharani Imran (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Hospital public relations face significant challenges during the Covid 19 pandemic.The purpose of this study was to describe the public relations strategy to improve the imageand reputation of the hospital. This research uses a literature study. The findings of thisstudy are that hospital public relations can implement strategies to increase publicawareness, socialize hospital products and services, educate patients about maintainingtheir health, provide information about hospital excellence, build hospital trust andcredibility, apply a friendly and communicative hospital culture, motivate patients andbuild good relationships, and disseminate newsworthy information to the mass media.Hospital public relations should accelerate change, innovation and creativity incommunication.